2018
DOI: 10.2147/cmar.s163932
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis and effects of local treatment strategies for orbital embryonal rhabdomyosarcoma: a population-based study

Abstract: IntroductionOrbital embryonal rhabdomyosarcoma is a rare childhood malignancy with a good prognosis, but the optimal treatment remains unclear. Using a population-based cancer registry, we assessed the prognoses and survival outcomes of patients with orbital embryonal rhabdomyosarcoma according to the local treatment strategy.Patients and methodsPatients diagnosed with orbital embryonal rhabdomyosarcoma between 1988 and 2012 as part of the Surveillance Epidemiology and End Results program were included. Univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, since 2004 the Collaborative Staging Codes were included, which gives clinical and pathologic data that was not previously available. Surgical details also have varied throughout the time period of this database, with recent years including more specifics of the surgeries performed . The lack of these critical details in the earlier years of the database limits the ability to analyze them when the goal is to have a large cohort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, since 2004 the Collaborative Staging Codes were included, which gives clinical and pathologic data that was not previously available. Surgical details also have varied throughout the time period of this database, with recent years including more specifics of the surgeries performed . The lack of these critical details in the earlier years of the database limits the ability to analyze them when the goal is to have a large cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies investigating rhabdomyosarcoma demographics and prognostic factors using databases have largely focused on specific anatomic sites or JOURNAL OF ORTHOPAEDIC RESEARCH ® OCTOBER 2019 subtypes. 3,4,6,[14][15][16][17][18][19][20] In a 2017 study by Nasioudis et al 15 rhadomyosarcoma of the lower female genital tract was shown to be most prevalent in prepubertal girls and adolescents, but carry excellent survival rates. Additionally, rare cases affecting adults resulted in poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,5 RMS most commonly involves the retrobulbar region but can involve other areas, including eyelids, conjunctiva, and rarely, uveal tissue, often manifesting as rapidly progressive proptosis or globe displacement. 6,7 We are reporting this case because: rare bilateral orbital RMS with a very aggressive course in an uncommon age group; bilateral proptosis, and simultaneous confusion secondary to temporal lobe abscess in one diagnosis.…”
Section: Introductionmentioning
confidence: 97%
“…Little studies focus on the treatment for orbital sarcoma, except for pediatric rhabdomyosarcoma, which is the most common pediatric orbital malignant tumor [4] . Previous studies convinced rhabdomyosarcoma including orbital lesions was relatively sensitive to chemotherapy and irradiation [5][6][7] . For most types of NRSTSs, surgery with wide margins remains the cornerstone of curative intent treatment, however, wide margins in the orbit are often difficult to achieve due to the proximity of vital structures or the destruction of appearance.…”
Section: Introductionmentioning
confidence: 99%